Structure and electronic properties of calcium doped ybco-247 superconductor via density functional theory / Mohd Shafiq Afnan Ali - Ali, Mohd Shafiq Afnan (2020)
The effect of doping calcium to Y-247 superconductor was studied via Density Functional Theory through the electron density of a material at ground state due to Hohenberg-Kohn and Kohn-Sham theorem respectively. Calcium was used as a dopant to substitute Cu2+ and Y3+ that possibly increases the hole concentration. It was found that direct substitution into the Cu-site of cuprate superconductors will directly affect its properties. Density Functional Theory (DFT) calculation was used as the simulation platform to calculate the energy band gap, density of states and the electron density of the Y-247 phase. The structure retains it orthorhombicity when doped at both side but decreases the lattice parameter c. An increase in energy band gap above the Fermi level can be seen as the concentration increase from x=0.02, x=0.04, x=0.06, x= 0.08 to x=0.10 for Ca-doping into Y-site of the system. Ca-doping into Cu-site shows a decrease in the energy band gap when the value of dopant increases. Doping Ca into Y-site shows an increase in the density of state with value x=0.02 and x=0.04 but started to decrease at x=0.06. In Cu-site, doping concentration of x=0.04 shows the highest at partial density of state of oxygen 2p orbital. The electron density distribution show a steady distribution along CuO chain and CuO2 plane which shows high probability of electron existence which proves the superconducting properties at the CuO2 plane and CuO chains respectively as the charge carriers.